The Technique of Al’ab Al-Lughawiyah in Teaching Arabic in an Islamic Elementary School - Alrasi, Fitri; Fakhrin, Nurul; Wahdi, Rifana; Harum Pratiwi, Sekar (Khalaqa: Journal of Education and Learning, 2023)
The background of this research is the difficulty in understanding Arabic learning by students class III SDIT Al Fityah School, Solok City, which is caused by students’ interest and motivation towards learning Arabic. Therefore a teacher must be precise in choosing and determining Arabic teaching strategies in the teaching and learning process, because the subject matter delivered without regard to learning strategies will actually make it difficult for the teacher to achieve the learning objectives. This study aims to find out the various al’ab al-lughawiyah strategies used, how the implementation of al’ab al-lughawiyah, and what the learning outcomes, are when al’ab al-lughawiyah is applied to the learning process in class III SDIT Al Fityah School. This research uses reservation, interview and documentation techniques. The data analysis technique used in descriptive qualitative analysis which consists of three activities that take place simultaneously, namely data reduction, data presentation, and drawing conclusions. The results of this study were that students in class III SDIT Al Fityah School, Solok City, showed better learning outcomes and students grades increased..